1974
DOI: 10.1017/s0003356100017384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crossbreeding and inbreeding on the frequencies of blood groups in three breeds of sheep

Abstract: Blood groups were determined for eight loci in a total of 742 sheep and for the Tf (transferrin) locus of 512 sheep comprising the Scottish Blackface, the Cheviot and the Welsh Mountain breeds and their crosses. Each breed and cross was represented by a noninbred F2 generation and by three stages of inbreeding (25, 37-J-and 50%). The loci for which all genotypes were distinguished were Hb, M, and Tf, and those for which partial description (including the recessive homozygote) was made were A, B, C, D, R and i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…Significance of dif@rences among czasseS of inbmeding chf = 9.77, grounds (Falconer 1960) and observed in practice in Scottish hill sheep (Rasmusen et al 1974) as well as in the present study (Table 8).…”
Section: Test F O R Significance Of Differences (Chi2 Approximation Osupporting
confidence: 65%
See 1 more Smart Citation
“…Significance of dif@rences among czasseS of inbmeding chf = 9.77, grounds (Falconer 1960) and observed in practice in Scottish hill sheep (Rasmusen et al 1974) as well as in the present study (Table 8).…”
Section: Test F O R Significance Of Differences (Chi2 Approximation Osupporting
confidence: 65%
“…A record can be made of the frequencies of certain alleles, and future workers would then be able to compare these frequencies with contemporary records to check whether genetic conservation had been achieved. Many protein polymorphisms exhibit codominance, i.e., the heterozygous form can be distinguished from the homozygous, and when they are investigated in pedigree populations (Rasmusen et al 1974) they make it possible to observe the reduction in heterozygosity which is the predicted consequence of inbreeding.…”
Section: Introductionmentioning
confidence: 99%
“…They further indicated that this could be related to the environment. On the other hand, Rasmussen et al (1974) observed that in some British sheep breeds and their crosses inbreeding had the effect of decreasing heterozygosity roughly in relation to expectation. Curvilinearity of the effect of inbreeding on economic traits has been reported in other species (Dinkel et al 1968) while Bereskin et al (1968) demonstrated that the equation representing the relationship between 154-day litter traits in pigs and inbreeding of the 1-2 litter was cubic.…”
Section: Inbreedingmentioning
confidence: 72%
“…(1963) identified the frequency of transferrii types and alleles in a flock of Welsh Mountain Sheep, and Rasmusen et al (1974) typed three breeds of sheep, Welsh Mountain, Cheviot and Scottish Blackface, with respect to transfenin types. Taking the data given by Rasmusen et al (1974), it would appear that the Herdwick Sheep at Compton are somewhat similar to the Scottish Blackface, having T f B and T f D present at the highest frequency, with Tf4 and Tfc present at a very low frequency, and an absence of the TfE allele. Whether conclusions can be drawn as to the origins of the two breeds being common it is not possible to state until other genetic parameters in the blood can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is the ,problem of generality within one breed. The data on the transferrin types in the Welsh Mountain Sheep from the two sources (Khattab et al, 1963;Rasmusen et al, 1974) give varying frequencies for the transferrin types but they do have the same trend in the frequencies. The foundation flock of Herdwicks at Compton originated from five individual flock obtained over a wide area, and can therefore be considered to be genetically diverse.…”
Section: Discussionmentioning
confidence: 99%